Relación entre características sociodemográficas y riesgo de depresión posparto en puérperas que consultan en la clínica CORPOMEDIC Tarapoto Junio-Setiembre 2012 - Vasquez Julcahuanga, Elen Rosa (2012)
This research entitled “related between sociodemographic characteristics and postpartum depression in postpartum women who consult CORPOMEDIC Clinic. Tarapoto district. June-September 2012”; it was planned as descriptive correlational cross-sectional, with a quantitative approach, it aimed to determine the relationship between sociodemographic characteristics and postpartum depression in postpartum women who came to the Clinic CORPOMEDIC Tarapoto. The sample was represented by 30 postpartum women who met the inclusion criteria. For data collection technique was used as the questionnaire and two instruments: a structured interview to identify the sociodemographic characteristics of postpartum women and standardized test of closed questions; Scale Edinburgh Postnatal Depression (EPDS), which was previously requested the author to identify the risk of depression in postpartum women. The data were systematized using the statistical package SPSS Microsoft Excel 2007 and Version 17.0. The findings were: increased risk of postpartum depression in postpartum women was 66.7% and 33.3%) had no risk of depression. 73.3% of students had between 20 to 30 years old, 80% had stable union, 36.7% were housewives, 50.0% primiparous, 46.7% reported having one child, the 30.0% had completed high school, 40.0% had incomes between 501 to 750 soles, 60.0% reported unwanted pregnancy and 56.7% had cesarean delivery. There was no significant association between postpartum depression and sociodemographic characteristics: age, marital status, occupation, parity, number of living children, educational level and income level, but found a significant association between Postpartum Depression Pregnancy and the type and significant association between postpartum depression and the type of delivery, postpartum clinic in Tarapoto-CORPOMEDIC.